Opioids in the treatment of non-specific acute and chronic pain - Dmytriiev, D V; Zaletska, O A; Bortnik, D I (Pain medicine, 2019)
After reading this article, the reader will be familiar with the general classes of opioid agonists and partial agonists, the basics of the pharmacokinetics and pharmacodynamics of opioids, the risks of opioid therapy and the requirements for the safe and effective use of opioids in acute and chronic pain. The use of opioids during surgical procedures or anesthesia is not discussed. Also, there is no discussion about various available opioid antagonists that are used to treat overdose and the various disorders associated with their use (including naloxone and naltrexone). Opioids are available, the most powerful and effective analgesics, and have become acceptable drugs for the treatment of acute and cancerous pain. However, there is concern about their use in case of chronic pain, if there is no cancer, because they are long-range ineffective but best suited for stopping this pain. Opioid prescription must be monitored for better use. Chronic pain creates discomfort for these patients, reducing their productivity and efficiency, which, in turn, can lead to economic problems in the country. The choice of Nalbuphine is due to the following reasons: the opioid, which is comparable to morphine by its analgesic potential, but has a better safety profile for nausea, vomiting and respiratory depression; not subject to strict quantitative accounting (extract on prescription form 1); the choice of opioid analgesics is significantly limited in Ukraine.